A study on the Nominal Plural forms in early middle English - Dr.Siraj Ahmad Rather (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2017)
Nominal plural forms were not common in old English. Old English noun usually inflected as a strong neuter, the plural form being win. The s – form in the text is perhaps one of the earliest instances of transfer to –s and comes straight down to later periods, seeing that the s – form is the only accepted plural. The second point is s – ending extends to historically unexpected classes of nouns. Examples are burgas, degles, feondas, Rondas, hoses etc. The number of nouns that transferred to – s may not be very large, but the examples show that this is a preliminary stage to the further development in early Middle English. The present nominal plural forms describe how the old English changed into early Middle English.